2019
DOI: 10.1186/s40104-019-0378-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of live yeast on differential genetic and functional attributes of rumen microbiota in beef cattle

Abstract: Several studies have evaluated the effects of live yeast supplementation on rumen microbial population; however, its effect on differential microbial genes and their functional potential has not been described. Thus, this study applied shotgun metagenomic sequencing to evaluate the effects of live yeast supplementation on genetic and functional potential of the rumen microbiota in beef cattle. Eight rumen-cannulated Holstein steers were randomly assigned to two treatments in a cross-over design with two 25-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 34 publications
(42 reference statements)
4
24
0
Order By: Relevance
“…To the best of our knowledge, this was the first study that attempted to investigate the effects of S. cerevisiae -based DFM on the relative abundance of transcriptionally active members and functional attributes of the rumen microbiota in beef cattle that were fed a corn silage-based diet. Several previous studies that evaluated the effects of S. cerevisiae -based DFM on rumen microbial population, focused on the taxonomic abundance of rumen microbial population [ 4 , 30 , 31 ]. In our companion study [ 7 ], we analyzed the effects of supplemental PROB and SYNB on the relative abundance of ruminal bacterial via 16S rRNA gene sequencing and observed that, compared to CON, supplemental PROB altered the relative abundance of Succinivibrio , Rikenellaceae RC9 gut group, Succiniclasticum , Prevotella 1, and Prevotellaceae UCG-001, whereas SYNB altered the relative abundance of Succinivibrionaceae UCG- 001, Succiniclasticum , Prevotella 1, and Prevotellaceae UCG-001.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To the best of our knowledge, this was the first study that attempted to investigate the effects of S. cerevisiae -based DFM on the relative abundance of transcriptionally active members and functional attributes of the rumen microbiota in beef cattle that were fed a corn silage-based diet. Several previous studies that evaluated the effects of S. cerevisiae -based DFM on rumen microbial population, focused on the taxonomic abundance of rumen microbial population [ 4 , 30 , 31 ]. In our companion study [ 7 ], we analyzed the effects of supplemental PROB and SYNB on the relative abundance of ruminal bacterial via 16S rRNA gene sequencing and observed that, compared to CON, supplemental PROB altered the relative abundance of Succinivibrio , Rikenellaceae RC9 gut group, Succiniclasticum , Prevotella 1, and Prevotellaceae UCG-001, whereas SYNB altered the relative abundance of Succinivibrionaceae UCG- 001, Succiniclasticum , Prevotella 1, and Prevotellaceae UCG-001.…”
Section: Discussionmentioning
confidence: 99%
“…Saccharomyces cerevisiae is capable of de novo biosynthesis of co-enzyme A, via the activities of dephospho-CoA kinase [ 38 ]. The results of our previous study [ 4 ] demonstrated that coenzyme A biosynthesis pathway was enriched in the rumen of beef steers fed diet supplemented with a S. cerevisiae -based additive. Thus, it is reasonable to infer that supplemental PROB and SYNB stimulated the conversion of succinate to propionate via biosynthesis of coenzyme A, which catalyzes the conversion of succinate to methylmalonyl-CoA and then to proponyl-CoA, which is subsequently converted to propionate [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ogunade et al . [ 45 ] stated that yeast S. cerevisiae at the dosage 15 g/day might increase the amount of ruminal CH 4 produced in steers in a 25-day long experiment due to the increased abundance of M. ruminantium . Ding et al .…”
Section: Discussionmentioning
confidence: 99%